Effect of polymeric stabilizers on the size and stability of PLGA paclitaxel nanoparticles - Mirina Sakhi; Abad Khan; Ismail Khan; Saeed Ahmad Khan; Sumaira Irum Khan; Muzna Ali Khattak; Mohammad N. Uddin; Mohsin Kazi; Fazli Nasir (Elsevier, 2023)
The aim of this study is to formulate polymeric paclitaxel nanoparticles with various stabilizers to improve solubility, enhance stability, maximize therapeutic efficacy and minimize detrimental toxicities of paclitaxel. In this study, trastuzumab-guided poly lactic-co-glycolic acid (PLGA)-loaded paclitaxel nanoparticles were formulated with pluronic F-127, polyvinyl alcohol (PVA), poloxamer 407, Tween-80, span 20, sodium dodecyl sulfate (SDS), and sodium lauryl sulfate (SLS) at different concentrations (0.5, 1, 1.5 and 2%) using the solvent evaporation method. The nanoparticles were evaluated for physicochemical characteristics and short and long-term stability. The optimum particle size (190 nm ± 12.42 to 350 nm ± 11.1), PDI (0.13 ± 0.02 to 0.2 ± 0.01), surface charge (-19.1mv ± 1.5 to −40.4mv ± 1.6), drug loading (2.43 to 9.5 %) and encapsulation efficiency (greater than 80 %) were obtained with these stabilizers while keeping the polymer concentration, temperature, probe size, amplitude and sonication time constant. The nanoformulations were stably stored at 4 °C. The nanoformulations of paclitaxel with pluronic F-127, polyvinyl alcohol (PVA), and poloxamer 407 were found to be more soluble, stable, uniform in physicochemical properties, and efficient in drug loading and encapsulation for improved therapeutic effects.